2017
DOI: 10.4183/aeb.2017.294
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of VDR Promoter Methylation, CDX-2 VDR Polymorphism and Vitamin D Levels in Male Infertility

Abstract: Introduction. Vitamin D (VD) levels were correlated with different health conditions, including reproductive disorders in males. Vitamin D action is mediated through vitamin D receptor (VDR), which acts as a transcription factor. VDR gene promoter is embedded in a GC-rich island. The VDR gene has been shown to have several polymorphisms that affect the receptor function.Aim. To examine the relationship between Cdx-2 polymorphism (rs17883968), the methylation status of VDR's promoter and serum levels of 25-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Consistent with the current results, Vladoiu et al. (2017) and Hussain et al. (2018) found that serum levels of VD were significantly lower in infertile compared to fertile group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the current results, Vladoiu et al. (2017) and Hussain et al. (2018) found that serum levels of VD were significantly lower in infertile compared to fertile group.…”
Section: Discussionsupporting
confidence: 92%
“…Results of the present study were in accordance with Vladoiu et al. (2017), who were the first to assess seminal methylation of VDR gene in male infertility. The methylation of the VDR gene was found to be significantly higher in infertile patients compared to fertile group ( p = .0335).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A recent study conducted on infertile males who underwent oral supplementation with micronutrients in support of folate, B vitamins, zinc, and cysteines reported an increase in DNA methylation levels, resulting in improved sperm nuclear maturation and antioxidant defenses, with a possible positive effect on reproductive function (Bassiri et al, 2020). Furthermore, evidences on sperm DNA from infertile males indicate a high methylation of vitamin D receptor promoter in vitamin D-deficient conditions, thus suggesting the role of diet in epigenetic modifications and male reproductive dysfunction (Vladoiu et al, 2017). Similarly, one investigation indicated that parental diet can modulate the methylation levels of several genes, including liver-specific genes involved in cholesterol/lipid metabolism, whereas no effect of paternal diet on sperm DNA methylation was found in other studies (Carone et al, 2010;Rando and Simmons, 2015;Shea et al, 2015;Whitelaw, 2015).…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…The most prevalent polymorphisms include VDR-FokI, VDR-BsmI, VDR-TaqI, VDR-ApaI, and CDX-2 VDR [21]. The effect of Cdx2 polymorphism on infertility was examined by Vladoiu et al, and as a result, a significant association was detected [22].…”
Section: Discussionmentioning
confidence: 99%